(untitled) (Research, Society and Development, 2023)
The objective of this study was to analyze the emission of greenhouse gases through the diffusion flow of CO2 in the water-atmosphere interface of four urban streams, which flow into one of the main rivers of the Pantanal (River Paraguay). For this, we used a floating chamber on aquatic macrophytes and in an open water, considering the flow (emission and/or absorption) of CO2. The field campaign was carried out in the wet season (February) and dry season (September) in the Pantanal. During the rainy season, the streams had between 5 and 40% of vegetation cover, while in the dry season it was 80 to 100%. The rainy season presented an emission about twice as high as in the dry season (5.180,64 ± 8.196,20 mg m-2 day-1 and 2.654,92 ± 7.190,64 mg m-2 day-1, respectively). Only in one of the analyzed streams, it was not possible to find absorption of CO2 by macrophytes, while the other three showed absorption by these plants. These environments are quite neglected, however, in tropical environments they demonstrate an important role as contributors to the reduction of greenhouse gases and can help in carbon storage and nutrient cycling. In these places, aquatic macrophytes are important for CO2 reduction and can be better exploited for landscaping and as a source of atmospheric carbon reduction.